Shareholder protection in close corporations and the curious case of Japan : the enigmatic past and present of withdrawal in a leading economy - Koh, Alan K. (2022)
Oppressed, outvoted, and outgunned, minority shareholders have an obvious solution for their woes: vote with their feet, sell their shares, and leave the company. But this “Wall Street Rule” is only available to shareholders in publicly listed corporations; shareholders in close corporations—privately owned business entities with no market for their shares—do not have the option of easy exit. Legal solutions which enable the shareholder to voluntarily exit a company with their capital such as the oppression or unfair prejudice remedies in US and Anglo-Commonwealth corporate law—what this Article classifies as “withdrawal remedies”—are therefore vital in close corporations. However, until relatively recently, shareholders in Japan’s close corporations had no access to withdrawal under corporate law, as neither of Japan’s then-dominant close corporation forms offered it. By revealing how shareholder litigants, attorneys, and judges in Japan responded to the absence of withdrawal, this Article shows how Japan’s experience was no outlier among nations, but instead powerfully demonstrates the importance of withdrawal remedies in practice. Later, withdrawal remedies at law for close corporations became available in Japan for the first time with the watershed Kaisha-hō (Companies Act) of 2005, which introduced a new close corporation form, the Gōdō Kaisha (GK). This Article analyzes the challenges facing Japan’s new withdrawal regime and shows how comparative corporate law—armed with the law and experience of withdrawal in the United States, the United Kingdom, and Germany—offers valuable insights for the development of withdrawal in the world’s second largest developed economy.